ANALISIS KESESUAIAN LAHAN UNTUK LOKASI PERMUKIMAN DI KECAMATAN AUR BIRUGO TIGO BALEH KOTA BUKITTINGGI - Jhorgy Harlen Julio; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This research aim to (1) analyzing the suitability of residential land in the Aur Birugo Tigo Baleh, Bukittinggi city (2) this study aims to make a map the suitability of residential land in the Aur Birugo Tigo Baleh to the spatial pattern of the city of Bukittinggi. This research used descriptive quantitative method. The data analysis techniques used are land suitability analysis, land suitability analysis for spatial patterns, and area function analysis. Based on the results of the study, it was found that (1) Not all land for settlements is suitable for Aur Birugo Tigo Baleh based on parameters that have been determined using boolean, there are two land functions, namely land that is suitable and land that is not suitable for settlement (2) Directions for developing residential land There are two categories, namely, land that can be developed and land that cannot be developed, land that can be developed is 64 hectares(Appropriate/S2 covering an area of ​​44 Ha, and Marginal Appropriate/S3 covering an area of ​​20 Ha) designated as a planned residential area based on the RTRW of the area, while land that is not suitable for development is 490 hectares (Not Appropriate Now/N1 area of ​​490 Ha).